Exploring the Sodium‐Storage Mechanism of Nanosized Disodium Rhodizonate as the Anode Active Material. (4th February 2022) - Hao, Zhiqiang; Dimov, Nikolay; Nishio, Akira; Sakamoto, Ryo; Okada, Shigeto
Abstract: Nanosized disodium rhodizonate (Na2 C6 O6, NCO) prepared by antisolvent crystallization is tested as an organic anode material for sodium‐ion batteries (SIBs). A reversible capacity of 230 mAh g −1 combined with an excellent capacity retention of ≈85% after 1000 cycles versus Na/Na + is demonstrated in a NaPF6 ‐DME electrolyte. Such a promising electrochemical performance is achieved by the synergy of the NCO particle nanosizing, and the formation of a thin, but stable and Na + ‐permeable solid electrolyte interface layer that builds‐up readily in the NaPF6 ‐1, 2‐dimethoxyethane electrolyte. The feasibility of the nanosized NCO anode for SIBs is also confirmed in a full sodium‐ion cell versus Na3 V2 (PO4 )3 cathode, and the discharge potential is as high as 2.0 V suggesting a promising energy density. Abstract : Na‐doped sodium rhodizonate Na4 C6 O6 is used as an anode for sodium‐ion batteries for the first time. Reasonable rate performance and cycle life in full cell configuration confirm the feasibility of sodium rhodizonate as an anode for sodium‐ion batteries for sodium uptake Na4 + x C6 O6 (x≤2).